2 Pharmacological inhibition of sarcolemmal fatty acid uptake provides a novel mechanism to improve metabolism and function in the type 2 diabetic heart. (17th November 2015) - Fialho, MdL Sousa; Mansor, LM; Yea, G; Evans, RD; Coumans, WA; Luiken, JJ; Glatz, J; Tyler, DJ; Heather, LC
Abstract : Aims: The type 2 diabetic heart is metabolically abnormal, which has been implicated in decreased recovery of diabetic hearts post-ischaemia. We propose that reducing sarcolemmal fatty acid uptake, by inhibiting fatty acid translocase (FAT/CD36), may provide a novel mechanism to rebalance metabolism, and hypothesise this may improve function in the diabetic heart. Methods: Type 2 diabetic and control rat hearts were perfused under normoxia, hypoxia, and reoxygenation, with radioactive substrates for measurement of metabolism in the contracting heart. The FAT/CD36 inhibitor sulfo-N-succinimidyl oleate (SSO) was infused 5 min prior to hypoxia. Results: In normoxia, diabetic hearts had increased fatty acid oxidation rates (39%) and decreased glycolysis (59%) compared with controls. During hypoxia, fatty acid oxidation was suppressed to low levels in all hearts, however, diabetic hearts did not concomitantly upregulate anaerobic glycolysis to the same extent as controls. During reperfusion, metabolism returned to normoxic rates, but was accompanied by a 55% increase in myocardial lipids in diabetic hearts. Infusing SSO prior to hypoxia increased glycolysis in diabetic hearts. SSO reduced fatty acid oxidation rates in diabetic hearts to control levels at reoxygenation, accompanied by prevention of excess myocardial lipid deposition. These metabolic changes resulted in a 27% improvement in contractile recovery in diabetic hearts treated with SSO. Conclusions: Diabetic hearts have limited metabolic flexibility when challenged with hypoxia, which can be rapidly rectified by reducing fatty acid uptake with the FAT/CD36 inhibitor, SSO. This novel approach provides a mechanism to prevent lipotoxicity and improve contractile function in the diabetic heart.